2020
DOI: 10.1016/j.jim.2019.112687
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel biomarkers in HCV positive patients with mixed cryoglobulinemia

Abstract: Background: Infections, autoimmunity and cancer play a role as determinants of etiology in Hepatitis C virus (HCV) related mixed cryoglobulinemia (MC). Several factors of risk have been suggested as markers of pathogenesis and progression of HCV-related MC into B cell Non-Hodgkin's Lymphoma (B-NHL). Here, we evaluated IgG subclass distribution, free light chains (FLCs) and vascular endothelial growth factor (VEGF) as a new combination of biomarkers. Methods: We measured IgG1-4 subclasses, FLCs and VEGF levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…2C): in our hands, VEGF levels seem to follow the ingravescence status of disease (HCV‐MC > HCV naïve), without being affected by RTX infusion even for those patents resulting in remission after treatment. Our findings confirm the role of VEGF as a sentinel biomarker of disease activity and presence of complications, as already suggested and reported in other clinical settings [35, 42, 51]; overall, analysis of VEGF may be useful in the clinical practice for evaluation of patients with autoimmune/inflammatory disorders. The underlying mechanism of impaired VEGF‐dependent angiogenesis that may drive the evolution of a small‐vessel vasculitis into an overt B‐cell non‐Hodgkin's lymphoma remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2C): in our hands, VEGF levels seem to follow the ingravescence status of disease (HCV‐MC > HCV naïve), without being affected by RTX infusion even for those patents resulting in remission after treatment. Our findings confirm the role of VEGF as a sentinel biomarker of disease activity and presence of complications, as already suggested and reported in other clinical settings [35, 42, 51]; overall, analysis of VEGF may be useful in the clinical practice for evaluation of patients with autoimmune/inflammatory disorders. The underlying mechanism of impaired VEGF‐dependent angiogenesis that may drive the evolution of a small‐vessel vasculitis into an overt B‐cell non‐Hodgkin's lymphoma remains to be determined.…”
Section: Discussionsupporting
confidence: 91%
“…The prognostic association of elevated VEGF levels with worsening outcome has been reported for SARD patients as well as for malignant blood diseases [35, 50]. In a recent research paper, we already analyzed VEGF serological levels in HCV‐related MC patients: we found a positive correlation of raised VEGF levels with both k and λ FLCs suggesting that the strong viral‐driven B activation could be worsening into lymphoproliferative disorders [51]. Here, analyzing the effects of RTX, we showed that our population of HCV‐MC patients displayed very high VEGF serological levels, without significant reduction following RTX treatment (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, the κ/λ ratio can be useful for monitoring therapeutic outcomes thanks to the predictive role of FLCs because the FLC ratio falls within the reference limits during treatment with specific antiviral drugs [41] . The analysis of sera from a larger group of HCV-MC patients in comparison to HCV-negative patients with a systemic autoimmune disorder confirmed that HCV-MC is associated with high levels of serum FLCs comparable to those in autoimmune disorders, underlying the strong correlation with B-cell hyperactivity in both diseases [89] .…”
Section: Introductionmentioning
confidence: 68%
“…During the process of immunoglobulin synthesis, plasma cells produce light chains in excess of intact immunoglobulins that may be released into the circulation; FLCs should be considered bioactive molecules rather than a secondary product of the synthesis of Igs without any functional relevance. FLCs' role in course of autoimmune diseases has been deeply investigated [10][11][12][13]. The aim of the present study is to evaluate the diagnostic performance of saliva specimens measuring IgA and FLC levels to observe the trend of these markers in the course of the disease and to study the activation and involvement of oral immunity in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 98%